Damage-Associated Molecular Patterns in Myocardial Infarction and Heart Transplantation: The Road to Translational Success - Silvis, Max J. M.; Kaffka genaamd Dengler, Selma E.; Odille, Clémence A.; Mishra, Mudit; van der Kaaij, Niels P.; Doevendans, Pieter A.; Sluijter, Joost P. G.; de Kleijn, Dominique P. V.; de Jager, Saskia C. A.; Bosch, Lena; van Hout, Gerardus P. J. (Frontiers in Immunology, 2020)
In the setting of myocardial infarction (MI), ischemia reperfusion injury (IRI) occurs due to occlusion (ischemia) and subsequent re-establishment of blood flow (reperfusion) of a coronary artery. A similar phenomenon is observed in heart transplantation (HTx) when, after cold storage, the donor heart is connected to the recipient’s circulation. Although reperfusion is essential for the survival of cardiomyocytes, it paradoxically leads to additional myocardial damage in experimental MI and HTx models. Damage (or danger)-associated molecular patterns (DAMPs) are endogenous molecules released after cellular damage or stress such as myocardial IRI. DAMPs activate pattern recognition receptors (PRRs), and set in motion a complex signaling cascade resulting in the release of cytokines and a profound inflammatory reaction. This inflammatory response is thought to function as a double-edged sword. Although it enables removal of cell debris and promotes wound healing, DAMP mediated signalling can also exacerbate the inflammatory state in a disproportional matter, thereby leading to additional tissue damage. Upon MI, this leads to expansion of the infarcted area and deterioration of cardiac function in preclinical models. Eventually this culminates in adverse myocardial remodeling; a process that leads to increased myocardial fibrosis, gradual further loss of cardiomyocytes, left ventricular dilation and heart failure. Upon HTx, DAMPs aggravate ischemic damage, which results in more pronounced reperfusion injury that impacts cardiac function and increases the occurrence of primary graft dysfunction and graft rejection via cytokine release, cardiac edema, enhanced myocardial/endothelial damage and allograft fibrosis. Therapies targeting DAMPs or PRRs have predominantly been investigated in experimental models and are potentially cardioprotective. To date, however, none of these interventions have reached the clinical arena. In this review we summarize the current evidence of involvement of DAMPs and PRRs in the inflammatory response after MI and HTx. Furthermore, we will discuss various current therapeutic approaches targeting this complex interplay and provide possible reasons why clinical translation still fails.